The Management and Long-term Outcome of Traumatic Pancreatic Type Ⅲb Injuries - Ando, Yasuhisa; Okano, Keiichi; Asano, Eisuke; Uemura, Jun; Oshima, Minoru; Suzuki, Yasuyuki; Suto, Hironobu; Matsukawa, Hiroyuki; Noge, Seiji (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2019)
[Background] Diagnosis and selection of the optimal surgical procedure for traumatic pancreatic type Ⅲb injuries are difficult, and evaluation of short-and long-term outcomes are important. [Objective] We evaluated the treatment strategy with endoscopic retrograde cholangiopancreatography (ERCP) and the short-and long-term outcomes for traumatic pancreatic Ⅲb type injury cases. [Subjects and results] Nine patients underwent surgical treatment for traumatic pancreatic Ⅲb type injuries in our department from July 2007 to June 2018. The median age was 31 (8〜77) years. Two of the 9 cases (22％) were able to be diagnosed as having a main pancreatic duct injury from CT findings, Among 9 cases, the main pancreatic duct injury was diagnosed with CT in two cases, while it was diagnosed with ERCP in 7 cases, the injury was diagnosed in all cases. Four cases (44％) had a pancreatic fistula, and one case (11％) had bile leakage postoperatively. The median follow-up time was 57 months (5〜80 months). Four (50％) and 2 (25％) out of 8 cases performed pancreatoduodenectomy (PD) had stenosis of their choledochojejunostomy and pancreatojejunostomy anastomosis respectively and 2 (25％) underwent a reoperation for the treatment. [Conclusion] ERCP for traumatic pancreatic Ⅲb type injuries was more useful to evaluate the damage of the main pancreatic duct than CT. There were late complications in young cases, and this fact is a future issue.